Vote for Me! The Language of Persuasion Used by Philippine Presidentiables - Theresa Liquigan Eustaquio (Jurnal Studi Pemerintahan)
Words are a powerful tool in persuasion. This research presents a discourse analysis of the persuasion techniques in speeches of the ten Filipino presidentiables during the 2022 national elections in the Philippines. The data were analyzed by categorizing, organizing, and interpreting the techniques and its implication using the three levels of language of persuasion by The New Mexico Media Literacy Project (2007). Results revealed that the presidentiables positively benefited from the utilization of the techniques un- der the Intermediate level. This implies that this level effectively persuades Filipino voters for it requires more creativity from the politicians and less complex comprehension from the voters.